Advances in the natural history of urinary incontinence in adult females - Qianqian Li; Yun Cheng; Hongli Shi; Kaikai Xue; Fang Zhou (Taylor & Francis Group, 2023)
The aim of this review is to summarise the related characteristics of the natural history of female urinary incontinence (UI) using a narrative descriptive approach. PubMed, EMBASE and Web of Science were searched for articles published from 1 January 2010 to 1 January 2020 on the natural history of female UI, which including incidence, persistence, progression, remission, and regression of a single subtype of UI and the mutual influence of different UI subtypes. This literature review includes 15 articles published, indicates that UI is highly dynamic, with symptoms varying according to disease severity and subtype and influenced by multiple factors at different disease stages. Recent studies have increased our understanding of the natural history of UI. Future research should systematically analyse the progression of each subtype of UI and interactions between subtypes to prevent the progression of UI across females life course.